Agency and Paternalism: Balancing Acts Between a Domestic Violence Survivors’ Task Force and a State Coalition - Miller, Susan L. (Violence against women, 2021)
This research explores the dissonance between feminist ideology and practice as it manifests in an activist group of intimate partner violence/aggression (IPV/A) survivors under a state coalition on domestic violence serving multiple stakeholders. A gendered organizations framework reveals the activist group resisting paternalism and colonization in their efforts to achieve their goals and maintain their identity. Two-and-a-half years of observational field work reveals a complex dynamic, simultaneously feminist and patriarchal, with the activist group experiencing growing pains and internal conflict, emotion regulation, as well as empowerment. We offer suggestions for further exploration of the ways survivor–activist groups and coalitions can pursue collaborative partnerships.